PENGARUH KECERDASAN EMOSIONAL DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. RISMAWAN PRATAMA BERSINAR SUKABUMI - Firmansyah, Dery; Raspati, Galih; Hidayat, Erwin Rinaldy (JEBIM Prima, 2020)
The purpose of this study was to determine the effect of emotional intelligence and organizational commitment on employee performance at PT. Rismawan Pratama Shining Sukabumi. The design in this study uses a survey method with descriptive-quantitative approach and associative methods. To test the analysis of the research instruments used validity test, reliability test and classic assumption test, then to test statistical analysis and relationship analysis used Pearson product moment correlation, coefficient of determination, multiple linear regression and to test the hypothesis used the t test and F test. Based on the results of research that has been done, it can be seen that simultaneously emotional intelligence and organizational commitment significantly influence employee performance. By comparing Fcount with Ftable (183.9719 > 3.10), it means that H0 is rejected and H1 is accepted, so the research hypothesis proposed in this study is proven that emotional intelligence and organizational commitment together (simultaneously) affect the performance of employees. The magnitude of the contribution of the influence of emotional intelligence and organizational commitment to employee performance by 80.5%, while the remaining 19.5% is influenced by variables not examined